Βιβλιοκρισία: M. D. Lauxtermann - Μ. Whittow (eds.), Byzantium in the Eleventh Century. Being in Between, Papers from the 45th Spring Symposium of Byzantine Studies, Exeter College, Oxford, 24-6 March 2012 [Society for the Promotion of Byzantine Studies 19], London and New York, Routledge, 2017 - ΓΚΟΥΤΖΙΟΥΚΩΣΤΑΣ, Ανδρέας Ε. (Byzantina Symmeikta, 2021)
Βιβλιοκρισία: M. D. Lauxtermann - Μ. Whittow (eds.), Byzantium in the Eleventh Century. Being in Between, Papers from the 45th Spring Symposium of Byzantine Studies, Exeter College, Oxford, 24-6 March 2012 [Society for the Promotion of Byzantine Studies 19], London and New York, Routledge, 2017, σελ. xviii + 252. ISBN 978-1-138-22503-9